2021
DOI: 10.1186/s12877-021-02440-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and physical characteristics of locomotive syndrome stages as classified by the new criteria 2020 in older Japanese people: results from the Nagahama study

Abstract: Background The Japanese Orthopaedic Association (JOA) proposed the concept of locomotive syndrome (LS) in 2007 for detecting high-risk individuals with mobility limitation. In 2020, the JOA revised the clinical decision limits and introduced LS stage 3, which carried the highest-risk for LS compared to the conventional stages, 1 and 2. The purpose of this study was to characterize the prevalence, comorbidities, and physical characteristics in each LS stage, as per the LS criteria 2020. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 32 publications
5
34
2
Order By: Relevance
“…With a rapidly increasing old age population worldwide, the number of patients suffering from sarcopenia and disuse-induced muscular dystrophy is expected to increase. This leads to overall worse outcomes, requiring hospitalization, and increasing medical expenses and bed occupancy rates [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…With a rapidly increasing old age population worldwide, the number of patients suffering from sarcopenia and disuse-induced muscular dystrophy is expected to increase. This leads to overall worse outcomes, requiring hospitalization, and increasing medical expenses and bed occupancy rates [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Low back pain was strongly related to disc degeneration [ 42 ]. The presence of low back pain showed an association with the Loco-Check [ 16 , 42 ], GLFS-25 [ 18 , 19 , 20 , 21 , 22 , 23 ], GLFS-5 [ 24 ], Two-Step Test [ 25 ], and total assessment [ 26 , 27 ] ( Table 1 ). Furthermore, the degree of low back pain showed a positive association with the GLFS-25 score [ 20 , 21 , 22 , 23 ] and a negative association with Two-Step Test score [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a study conducted prior to the COVID-19 outbreak, Yoshimura et al used the GLSF-25 to determine LS prevalence rates of 59% and 33% in women and men in their 60s, respectively ( 17 ). Taniguchi et al reported a pre-outbreak LS prevalence rate of 42.1% in a 70–74-year-old cohort and 52.2% in a > 75-year-old cohort ( 18 ). As the present study included individuals aged over 65 years, the baseline LS prevalence of 41% before the outbreak (from March to April 2020) was not unexpectedly high.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with those of previous studies. Older age has been previously established as a risk factor for LS ( 10 , 16 , 18 , 19 ). Associations between LS and both low back pain and osteoarthritis of the knee and hip have also been reported ( 20 , 21 ).…”
Section: Discussionmentioning
confidence: 99%